2019
DOI: 10.17533/udea.rccp.v32n4a01
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ruminal bacteria in grazing Nellore steers

Abstract: Background: Rumen microorganisms have developed a series of complex interactions, representing one of the best examples of symbiosis between microorganisms in nature. Conventional taxonomic methods based on culture techniques are being replaced by molecular techniques that are faster and more accurate. Objective: To characterize rumen bacterial diversity of Nellore steers grazing on tropical pastures by sequencing the 16S rRNA gene using Illumina sequenctng. Methods: Three rumen-cannulated Nellore steers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…This might imply that the low-RFI steers could partition their methane production via alternative pathways especially when a lower proportion of H 2 and CO 2 is being produced during the fermentation process by the rest of microbiota. For instance, carbohydrates are fermented to propionic acid with no net loss of CO 2 and thus lower substrate for Methanobrevibacter to produce methane [ 32 , 33 ].Previous studies have shown that Methanobrevibacter are predominant methanogens in the rumen and their abundance has also been correlated with higher levels of methane emissions [ 34 , 35 ] and poorer feed efficiency [ 36 , 37 ]. Cattle with negative RFI phenotype have been reported to have reduced daily methane production [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might imply that the low-RFI steers could partition their methane production via alternative pathways especially when a lower proportion of H 2 and CO 2 is being produced during the fermentation process by the rest of microbiota. For instance, carbohydrates are fermented to propionic acid with no net loss of CO 2 and thus lower substrate for Methanobrevibacter to produce methane [ 32 , 33 ].Previous studies have shown that Methanobrevibacter are predominant methanogens in the rumen and their abundance has also been correlated with higher levels of methane emissions [ 34 , 35 ] and poorer feed efficiency [ 36 , 37 ]. Cattle with negative RFI phenotype have been reported to have reduced daily methane production [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota is composed of a set of thousands of species of microorganisms, consisting of bacteria, archaea, fungi, and protozoa [39,58]. At significant values, the bacteria represent the largest and most important ruminal microbial community, consisting of approximately 1.010 bacteria, 10 7 protozoa, 10 6 fungi per mL of rumen content [44], and 10 7 -10 8 cells per gram of ruminal content of methanogenic archaea [37,59].…”
Section: Rumen Microbiotamentioning
confidence: 99%
“…Gender-level taxonomic affiliations for readings generated from the 16S rRNA fragment sequences of bovine ruminal content using the Illumina platform. Adapted from Jesus et al[39].…”
mentioning
confidence: 99%